Surgical Treatment of Dacryocystitis by Using a Venous Catheter. Issue 4 (June 2020) - Meduri, Alessandro; Inferrera, Leandro; Tumminello, Giuseppe; Cicciù, Marco; Aragona, Pasquale
Abstract : Purpose: Aim of this work is to highlight the advantages of a new surgical technique performed over 15 patients affected dacryocystitis and treated by using a venous catheter. The arrangement of a 30 mm venous catheter used at the end of a dacryocystectomy (DCT) was performed in 15 patients with dacryocystitis. The venous catheter was removed at 30 days after the surgery. The use of the venous catheter allows washing the lacrimal drainage system, reducing the risk of postoperative infections and supports the recanalization of the lacrimal drainage system 30 days after surgery. The presented cases demonstrated how the technique is easy and it reduces the possibility of the post-operative infection. It could be performed under regional anesthesia. Furthermore, after the surgery the recanalization of the lacrimal drainage system with a significant reduction of the epiphora in 6 months after surgery has been observed.